Modelling and simulation of the ion exchange process for Zn2+(aq) removal using zeolite NaY (Research, Society and Development, 2021)
The treatment of water contaminated by toxic metals using ion exchange with zeolites is becoming attractive due to its low capital costs and high potential for removal capacity. Mathematical modelling of this process allows for operational control and estimation of the ability to remove these metals. In this work, the kinetic modelling was performed based on finite bath experimental data, with Intraparticle Diffusion (IPD) and External Liquid Film Mass Transfer (MTEF) models. The models Thomas (TH), Yoon-Nelson (YN) and Solid Film Mass Transfer (MTSF) were used to estimate the saturation time, ion exchange capacity and sizing variables of a fixed bed column. For the finite bath system, the results showed that the mass transfer was better represented by the IPD phenomenon. The breakthrough curve obtained by the Aspen Adsorption (MTSF) model presented the best fit, compared with experimental data, with R2≥0.9923. The average ion exchange capacities calculated for MTSF, TH and YN were respectively 2.22, 2.12 and 2.07 meq Zn2+(aq)/ g of zeolite. The model simulated with Aspen Adsorption was also used to analyze the continuous system behaviour, by varying the height of the bed. It was observed that increasing the height, the saturation time and ion exchange capacity also increase, while reducing the height makes axial dispersion the predominant mass transfer phenomenon, which reduces the diffusion of Zn2+(aq) ions.